Influence of mycorrhizal or microbial complex inoculation on laurustinus plants irrigated with reclaimed water. Issue 5 (2nd September 2020) - Gómez-Bellot, María José; Ortuño, María Fernanda; Álvarez, Sara; Sánchez-Blanco, María Jesús
ABSTRACT: The application of microorganisms in crops has been proposed as a strategy to cope with adverse environmental conditions. Two separate experiments (I and II) were carried out in laurustinus plants in field conditions. For each experiment, half of the plants were irrigated with control water (C, EC <0.9 dS m −1 ) and the other half with reclaimed wastewater (RW, EC: 6 dS m −1 ). In experiment I, for each irrigation treatment, half of the plants were inoculated with Glomus iranicum (AMF). In experiment II, for each irrigation treatment, half of the plants were inoculated with a rhizosphere microbial complex (RMC). In experiment I, AMF increased leaf Ca/Na ratio and reduced leaf Cl concentration. In addition, stem water potential was enhanced in plants subjected to RW. Stomatal conductance was also improved by AMF in plants subjected to C and RW treatments. In experiment II, leaf K/Na and Ca/Na ratios were increased and leaf Cl concentration was reduced by RMC. The RMC increased stem water potential and relative chlorophyll content in both irrigation treatments. Under RW irrigation, plants with RMC showed better leaf stomatal conductance. These results highlight the importance of studying the microorganisms/species interaction in order to select the best combination.